2015
DOI: 10.1308/003588414x14055925061036
|View full text |Cite
|
Sign up to set email alerts
|

Acute afferent loop syndrome in the early postoperative period following pancreaticoduodenectomy

Abstract: Acute ALS is a rare but important complication in the immediate postoperative period following PD and causes disruption to adjacent anastomoses, resulting in a bile leak. A prophylactic Braun anastomosis and wide mesocolic window may prevent this complication and subsequent deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Two retrospective cohort studies showed that the incidence of ALS in gastric cancer patients undergoing Billroth II and Roux-en-Y reconstruction was 1.01% and 0.2% respectively, and all were caused by adhesion, internal herniation, and peritoneal recurrence[ 1 , 2 ]. As for treatment, traditionally, surgery is the cornerstone of treatment for ALS, which includes converting a Billroth II to a Roux-en-Y[ 8 ], creating a Braun anastomosis between the afferent and efferent loops in a Billroth II[ 9 ], or excising redundant loops and reconstruction[ 10 ]. However, surgery is not suitable for every patient with ALS[ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two retrospective cohort studies showed that the incidence of ALS in gastric cancer patients undergoing Billroth II and Roux-en-Y reconstruction was 1.01% and 0.2% respectively, and all were caused by adhesion, internal herniation, and peritoneal recurrence[ 1 , 2 ]. As for treatment, traditionally, surgery is the cornerstone of treatment for ALS, which includes converting a Billroth II to a Roux-en-Y[ 8 ], creating a Braun anastomosis between the afferent and efferent loops in a Billroth II[ 9 ], or excising redundant loops and reconstruction[ 10 ]. However, surgery is not suitable for every patient with ALS[ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The afferent loop refers to the duodenojejunal loop proximal to the gastrojejunal anastomosis. 62 Its obstruction presents with abdominal pain and vomiting. On imaging, it appears as dilated fluid-filled tubular or C-shaped bowel (afferent limb/ loop) in the right upper quadrant or crossing the midline with transition in the region of anastomosis.…”
Section: Delayed Gastric Emptying: Incidence Of Delayed Gas-mentioning
confidence: 99%
“…Afferent loop syndrome (ALS) is a complication of Billroth II gastrojejunostomy (GJ), Roux-en-Y gastric bypass, and Whipple procedures. 1 , 2 Common causes include malignant infiltration, internal hernias, postsurgical adhesions, or intrinsic/extrinsic compression causing obstruction. 3 Symptoms include abdominal pain, distention, nausea, and vomiting.…”
Section: Introductionmentioning
confidence: 99%